Quarry Evaluation and Control of Bench Blasting - Sanga Tangchawal (Universitas Gadjah Mada, 2006)
Potential sites of quarries were evaluated by numerical rating techniques. There are 3 groups of implied rating factors on the rock deposits in surveyed quarry sites: the resource characteristics,resource economics, and the optimal excavation. A final resultfor each potential site wasrecorded and compared. In case of ongoing quarries, the planning steps for bench blasting were also suggested. By using the written packed program, the output results can be automatically demonstrated. Further trial processes can be done and the optimized blast plan view is obtained.